Pengaruh Harga dan Kelengkapan Produk terhadap Keputusan Pembelian Konsumen pada Hokky Mart Bima - Ikhwan; Kartin Aprianti (JOURNAL INTELEKTUAL, 2023)
Introduction/Main Objectives: This research aims to determine the influence of price and product completeness on consumer purchasing decisions at Hokky Mart Bima. Background Problem: That at Hokky Mart there are still some prices that are considered unaffordable and there are still other supermarkets that sell cheaper and there is still a lack of availability of goods for sale including a lack of complete brand variations. Novelty: Continuing further research on the same variables but locations with different problems. Research Method: The approach used in research is an associative approach. The sample in this study was 96 respondents. The data collection techniques used were observation, questionnaires and literature studies processed using SPSS version 20. Findings/Results: The results of the study show that price (X1) and product completeness (X2) are partially and simultaneously has a significant effect on consumer purchasing decisions at Hokky Mart Bima. Conclusion: Improving purchasing decisions can be done by increasing product completeness and appropriate pricing policies.